Identification of a Peptide for Systemic Brain Delivery of a Morpholino Oligonucleotide in Mouse Models of Spinal Muscular Atrophy - Shabanpoor, F; Hammond, S; Abendroth, F; Hazell, G; Wood, M; Gait, M (Mary Ann Liebert, 2017)
Splice-switching antisense oligonucleotides are emerging treatments for neuromuscular diseases, with several splice-switching oligonucleotides (SSOs) currently undergoing clinical trials such as for Duchenne muscular dystrophy (DMD) and spinal muscular atrophy (SMA). However, the development of systemically delivered antisense therapeutics has been hampered by poor tissue penetration and cellular uptake, including crossing of the blood-brain barrier (BBB) to reach targets in the central nervous system (CNS). For SMA application, we have investigated the ability of various BBB-crossing peptides for CNS delivery of a splice-switching phosphorodiamidate morpholino oligonucleotide (PMO) targeting survival motor neuron 2 (SMN2) exon 7 inclusion. We identified a branched derivative of the well-known ApoE (141-150) peptide, which as a PMO conjugate was capable of exon inclusion in the CNS following systemic administration, leading to an increase in the level of full-length SMN2 transcript. Treatment of newborn SMA mice with this peptide-PMO (P-PMO) conjugate resulted in a significant increase in the average lifespan and gains in weight, muscle strength, and righting reflexes. Systemic treatment of adult SMA mice with this newly identified P-PMO also resulted in small but significant increases in the levels of SMN2 pre-messenger RNA (mRNA) exon inclusion in the CNS and peripheral tissues. This work provides proof of principle for the ability to select new peptide paradigms to enhance CNS delivery and activity of a PMO SSO through use of a peptide-based delivery platform for the treatment of SMA potentially extending to other neuromuscular and neurodegenerative diseases.